1996
DOI: 10.1128/jb.178.2.332-339.1996
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of cyanelle peptidoglycan of Cyanophora paradoxa: a prokaryotic cell wall as part of an organelle envelope

Abstract: The peptidoglycan layer surrounding the photosynthetic organelles (cyanelles) of the protist Cyanophora paradoxa is thought to be a relic of their cyanobacterial ancestors. The separation of muropeptides by gel filtration and reverse-phase high-performance liquid chromatography revealed four different muropeptide monomers. A number of muropeptides were identical in retention behavior to muropeptides of Escherichia coli, while others had remarkably long retention times with respect to their sizes, as indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 44 publications
3
51
0
Order By: Relevance
“…These analyses provide substantial structural information derived from muropeptide-composition data. The sensitivity of this type of analysis has permitted the identification and qualification of peptidoglycan components down to the low level of 1-10 ng (Allmaier and Schimd, 1993), with successful results in the elucidation of peptidoglycan contained in the photosynthetic organelles (cyanelles) of the algae Cyanophora paradoxa (Pfanzagl et al, 1996). Nevertheless, no study has previously been performed that applied similar analytical procedures to characterize the peptidoglycan structure of intracellular bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses provide substantial structural information derived from muropeptide-composition data. The sensitivity of this type of analysis has permitted the identification and qualification of peptidoglycan components down to the low level of 1-10 ng (Allmaier and Schimd, 1993), with successful results in the elucidation of peptidoglycan contained in the photosynthetic organelles (cyanelles) of the algae Cyanophora paradoxa (Pfanzagl et al, 1996). Nevertheless, no study has previously been performed that applied similar analytical procedures to characterize the peptidoglycan structure of intracellular bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Glaucophytes are usually considered to be the earliest branch of the Archaeplastida because their plastids retain more ancestral features typical of cyanobacteria than are present in red algae or green plants; for example, peptidoglycan and carboxysomes [14,15]. Other characteristics that distinguish the Glaucophyta from the Rhodophyta and Viridiplantae include (i) the presence of a cyanobacterial-like fructose-1,6-bisphosphate aldolase, which was replaced by a duplicated cytosolic copy in the case of the other Archaeplastida lineages [144], (ii) lack of triple-helix chlorophyll-binding, light harvesting antenna complexes [145,146] and (iii) lack of plastidial phosphatetranslocator [20].…”
Section: Testing the Relationships Among Archaeplastida Lineagesmentioning
confidence: 99%
“…Glaucophyte plastids (called cyanelles) retain more cyanobacterial characteristics than do red alga and green plant plastids. The most remarkable is the presence of peptidoglycan, a typical component of bacterial cell walls located between the inner and outer membrane [14], as well as carboxysomes with enzymes involved in carbon fixation [15]. In addition, glaucophytes and rhodophytes still possess phycobilisomes, typical cyanobacterial photosystem II light-harvesting antennae [16].…”
Section: Introductionmentioning
confidence: 99%
“…The peptidoglycan of the glaucophyte plastid PGW [120] is characterized by the presence of N-acetylputrescine as the chemical substituent in half of the 1-carboxyl groups of the glutamic acid residues of the peptide chains [121,122]. Experimental studies have demonstrated that the biosynthesis of the peptidoglycan precursor (UDP-N-acetylmuramylpentapeptide) occurs in the glaucophyte plastid stroma, and that the assembly of the polymer network occurs in the periplasmic space [60,123].…”
Section: The Peptidoglycan Wall Of the Glaucophyte Plastidmentioning
confidence: 99%